New progress in the theoretical research and application of pulsating heat pipe - LI Qing-feng; WANG Ya-nan; HE Xin; LIAN Chen; LI Hua (工程科学学报)
As a new type of heat transfer device with a unique working mechanism, the pulsating heat pipe (PHP) has high heat transfer efficiency, high resistance capability to drying out, and good environmental adaptability. Its structure is simple and variable, and the cost is low. Thus, the pulsating heat pipe has a good value for practical application and is currently a research hotspot in the field of heat transfer technology. On the basis of the introduction of the general advantages, structure types, and working principle of the pulsating heat pipe, this study first summarized the structure models, such as the straight tube, single elbow tube, and partially single elbow tube, and the theoretical models, such as the mass-spring-damping model, mass-momentum-energy equation model, and other mathematical models, commonly used in the current theoretical modeling research. Then, the operational process, working mechanism, and latest research progress in pulsating heat pipes at home and abroad were reviewed from the aspects of experimental and computational visualization research. The influence of different design and use parameters, such as pipe diameter and length, shape of the section, heating method, filling rate, angle of inclination, input power, and type of working fluid, on the start-up performance, heat transfer performance, and heat transfer limit of the pulsating heat pipe was systematically introduced. Furthermore, from the design and application perspectives, the research on pulsating heat pipes applied in electronic equipment, solar energy collection, thermal management of power unit, and heat exchange in low-temperature environment was reviewed, and the effects and advantages of pulsating heat pipes in practical application were demonstrated. Finally, the future research directions and development trends were forecasted. It is pointed out that the working mechanism, working performance, working process, and optimization design method of pulsating heat pipes can be investigated through a more detailed theoretical and simulation modeling.